640 A hyperspectral index-based approach for in vivo automatic detection of skin tumors from hyperspectral images (Balneo and PRM Research Journal, 2024)
Skin cancer is the most common human malignancy and early diagnosis is important for successful treatment. Hyperspectral imaging provides both spectral and spatial information which may be useful for tumor diagnosis. In the present study, hyperspectral images of 36 skin tumors (seborrheic keratosis, actinic keratosis, basal cell carcinoma, squamous cell carcinoma) were acquired and analyzed. A skin cancer index was defined taking into account the differences in the angles made by the spectral slopes of the tumors and normal skin and the x axis in the spectral range (580-600) nm (where the differences in spectral signatures proved to be significant). When compared to histopathological diagnosis, the index allowed for differentiation between benign and malignant tumors and even between seborrheic and actinic keratosis or basal cell carcinoma and squamous cell carcinoma. Benign tumors had an index under 0.39999, while basal cell carcinoma ranged between 0.4000-0.59999, and squamous cell carcinoma between 0.6000-06999. In conclusion, the hyperspectral image-based skin tumor index is an objective method of identification and differentiation of skin tumors and may become a useful tool in their early diagnosisKeywords: skin cancer hyperspectral index, reflectance, slope, seborrheic keratosis, actinic keratosis, basal cell carcinoma, squamous cell carcinoma